Power Line Communication: Application In A Tether Based Underwater Vehicle. - Mohd Yusoff, Mohd Akmal; Zakaria, Muzammer; Nazeem, Alireza; Arshad, Mohd Rizal (2008)
This paper describes the potential usage and application of the Power Line Communication (PLC) in a tether based underwater vehicle as the alternative module in establishing the communication line.